Structure and sorption properties of multifunctional acrylic polymers designed for solid phase microextraction fibers. (2nd March 2020) - Jakubowska, Iwona; Popiel, Stanisław; Szala, Mateusz; Czerwiński, Michał; Chrunik, Maciej; Zasada, Dariusz; Marć, Paweł; Jaroszewicz, Leszek R.
Abstract: Polymeric materials are widely used because of their variety and modification ability. Multifunctional acrylates deserve special attention due to their feasibility of photopolymer development. We reported a new class of polymers produced by photopolymerization using VIS and UV radiation. Monomer mixtures consist of monomers, photo-initiators and co-initiators for VIS or monomers and photo-initiators for UV photopolymerization. One selected monomer was used in each mixture i.e. DTMPTA—trimethylolpropane tetraacrylate, TMPTA—trimethylolpropane triacrylate or TCDMA—tricyclodecanedimethanol diacrylate. Silicone oil terminated by hydroxyl groups—(OH–TSO) was used as the adjuvant sorption material. To characterise the physicochemical properties of obtained materials, instrumental analysis methods were applied. By using chromatographic analysis, it was shown experimentally that the new photopolymer materials have a high sorptive capacity and increased sorption selectivity towards selected organosulfur and organophosphorus compounds. This could result in the use of these new materials as sorption fibers used during solid-phase microextraction (SPME). Graphical abstract: Image 1 Highlights: Multifunctional acrylic monomers were used to produce new sorption materials. Photopolymerization with light of different wavelengths was used. Two different light sources were used during the polymerization. Polymers have great sorption properties in relation to selected CWAs simulants. These developed photopolymers could be used as SPME fiber coatings.